Unsteady bioconvective squeezing flow with higher‐order chemical reaction and second‐order slip effects. Issue 6 (5th April 2021) - Acharya, Nilankush; Bag, Raju; Kundu, Prabir Kumar
Abstract: In this investigation, the foremost aim is to study the impact of a higher‐order chemical reaction and second‐order slip on the bioconvective nanoliquid flow comprising gyrotactic microorganisms between two squeezed parallel plates. The existence of magnetic strength, thermophoretic, and Brownian migration is considered to model the flow. Similarity transformations are implemented to reduce our mathematical model into a set of nonlinear ordinary differential equations along with the requisite boundary conditions. The classical Runge‐Kutta‐Fehlberg method technique is employed to avail the numerical outcomes of the aforementioned nonlinear foremost equations correlated with the relevant boundary conditions. Parametric flow discussions, like, velocity profile, thermal profile, and heat and mass transport, have been portrayed through indispensable charts and graphs. Physical quantities, like, skin friction, Nusselt number, Sherwood number, and microorganism density number, have been estimated to analyze their numerous applications. The results communicate that temperature diminishes for squeezing factor and first‐order velocity slip parameter, but augments for second‐order slip parameter. Mass transport accelerates for chemical reaction but reduces for the order of reaction. Microorganism density number amplifies owing to chemical reaction and Peclet number while it decays for chemical reaction. This has advantageous applications in bio‐micro‐systems, bioreactors, biosensors, biochromatography, magnetic bioseparation devices, biocoating, and ecological fuels.